2006
DOI: 10.1136/gut.2005.076463
|View full text |Cite
|
Sign up to set email alerts
|

Surface expression and cytolytic function of natural killer cell receptors is altered in chronic hepatitis C

Abstract: The present study indicates that defective expression of NKR represents a novel mechanism contributing to impaired function of NK cells and CD8+ T cells in chronic hepatitis C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
206
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 209 publications
(229 citation statements)
references
References 40 publications
17
206
6
Order By: Relevance
“…3 The exact role of NK cells in HCV infection, however, remains elusive, because current studies have yielded inconsistent results regarding phenotype and function of NK cells. [4][5][6][7][8][9][10][11][12] For example, surface expression and function of NKp46, a major activating receptor, is discussed controversially. 5,[7][8][9]33 These discrepancies might, in part, be explained by different characteristics of study cohorts and/or methodological issues.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3 The exact role of NK cells in HCV infection, however, remains elusive, because current studies have yielded inconsistent results regarding phenotype and function of NK cells. [4][5][6][7][8][9][10][11][12] For example, surface expression and function of NKp46, a major activating receptor, is discussed controversially. 5,[7][8][9]33 These discrepancies might, in part, be explained by different characteristics of study cohorts and/or methodological issues.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] For example, surface expression and function of NKp46, a major activating receptor, is discussed controversially. 5,[7][8][9]33 These discrepancies might, in part, be explained by different characteristics of study cohorts and/or methodological issues. 28 Moreover, it is important to note that previous reports not only demonstrated varying expression of NKp46 in different NK-cell clones, but also suggested that density of NKp46 expression may correlate with cytolytic activity in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations